A molecular boron cluster-based chromophore with dual emission. Issue 45 (7th May 2020) - Anderson, Kierstyn P.; Waddington, Mary A.; Balaich, Gary J.; Stauber, Julia M.; Bernier, Nicholas A.; Caram, Justin R.; Djurovich, Peter I.; Spokoyny, Alexander M.
Abstract : Bromination of the luminescent borane, anti -B18 H22, via electrophilic substitution using AlCl3 and Br2, yields the monosubstituted derivative 4-Br- anti -B18 H21 as an air-stable crystalline solid. Abstract : Bromination of the luminescent borane, anti -B18 H22, via electrophilic substitution using AlCl3 and Br2, yields the monosubstituted derivative 4-Br- anti -B18 H21 as an air-stable crystalline solid. In contrast to the unsubstituted parent compound, 4-Br- anti -B18 H21 possesses dual emission upon excitation with UV light and exhibits fluorescence at 410 nm and phosphorescence at 503 nm, with Φ total = 0.07 in oxygen-free cyclohexane. Increased oxygen content in cyclohexane solution quenches the phosphorescence signal. The fluorescent signal intensity remains unaffected by oxygen, suggesting that this molecule could be used as a ratiometric oxygen probe.